Antithrombotic treatment pattern in newly diagnosed atrial fibrillation patients and 2-year follow-up results for dabigatran-treated patients in the Africa/Middle-East Region: Phase II results from the GLORIA-AF registry program. (June 2021) - Azar, Rabih R.; Ragy, Hany I.; Kozan, Omer; El Khuri, Maurice; Bazergani, Nooshin; Marler, Sabrina; Teutsch, Christine; Ibrahim, Mohamed; Lip, Gregory Y.H.; Huisman, Menno V.
Abstract: Background: Data on the epidemiology and treatment of atrial fibrillation in the Africa/Middle East region are limited, and the use of novel oral anticoagulants and their effectiveness in real-world clinical practice has not been evaluated. Methods and Results: This study used prospectively collected data from the Global Registry on Long-Term Oral Antithrombotic Treatment in Patients With Atrial Fibrillation (GLORIA-AF) to describe anticoagulant use and outcomes in Africa and the Middle East. Baseline characteristics of patients newly diagnosed with nonvalvular atrial fibrillation from Lebanon (242 patients, 40.3%), Saudi Arabia (236 patients, 39.3%), United Arab Emirates (87 patients, 14.5%), and South Africa (35 patients, 5.8%) were described, and clinical outcomes were investigated for all patients in this region who received dabigatran. In newly diagnosed patients (having a diagnosis within the last three months) with nonvalvular atrial fibrillation in Africa and the Middle East, the observed uptake of non-vitamin K oral anticoagulants was high in the first years following their availability; dabigatran was the most commonly used antithrombotic agent (314/600 patients), and only 1.5% of patients did not receive any antithrombotic therapy. Use of dabigatran was associated with a high persistence rate (>88% at 24 months) and low incidence rates of stroke, myocardial infarction, major bleeding, and all-cause mortality after 2 years of follow-up. Conclusions: Data from GLORIA-AF reveal a change in the landscape for stroke prevention in the AME region, and the results were consistent with those observed in the global GLORIA-AF registry, as well as those of randomized clinical trials. Clinical Trial Registration: NCT01937377 (https://clinicaltrials.gov/ct2/show/NCT01937377 ).